Peer-to-peer contact, social support and self-stigma among people with severe mental illness in Hong Kong. (September 2021) - Li, Xu-Hong; Zhang, Tian-Ming; Yau, Yuen Yum; Wang, Yi-Zhou; Wong, Yin-Ling Irene; Yang, Lawrence; Tian, Xiao-li; Chan, Cecilia Lai-Wan; Ran, Mao-Sheng
Background: Self-stigma exerts a range of adversities for persons with severe mental illness (SMI), however, little is known about the association between peer contact, social support and self-stigma. Aims: This study aimed to explore the mediating role of social support on the relationship between peer contact and self-stigma among persons with SMI in Hong Kong. Methods: A total of 159 persons with SMI (schizophrenia and mood disorder) in community service centres participated in the study through completing a survey on self-stigma, social functioning, social support, perception of peer contact and mass media. Logistic regression was utilised to explore the influencing factors of self-stigma among the participants. Results: The results showed that 81.1% of participants reported moderate to severe levels of self-stigma. Self-stigma was significantly associated with diverse factors (e.g. social functioning). Importantly, positive peer contact was significantly associated with lower self-stigma of persons with SMI. Social support acted as a mediator between peer contact and self-stigma. Conclusion: The results of this study suggest that contact-based interventions, such as enhancing positive peer-to-peer contact, should be conducted for reducing self-stigma among persons with SMI.